Viscoelastic damping of flexible risers: Theoretical model. (1st December 2020) - Liu, Junpeng; Ma, Jinsheng; Vaz, Murilo Augusto; Duan, Menglan
Abstract: Viscoelastic damping caused by the polymer in flexible risers may not be ignored to the global analysis in deep water, but because of its high complexity and non-linearity, damping value is generally hard to be observed. To identify and calculate the loss factor corresponding to viscoelastic damping, a theoretical model is developed by means of integration and iteration methods, in which, the fact that the gap between the adjacent layers changes over time is considered. This model also accounts for the effects of continuous temperature distribution in flexible risers. Case study shows that the gap between metal layer and polymetric layer is easy to appear and its values gradually increase instead of being constant. Compared with the previous model results, this model gives smaller equivalent axial stiffness but greater strain and viscoelastic damping. It is also found that, the larger loading frequency is, the smaller viscoelastic damping is. Highlights: A theoretical model is established to predict axisymmetric viscoelastic responses of flexible risers, where the continuous temperature field in cross-section is considered. An iterative algorithm is used for solving the theoretical model which considers the possible time-dependent gap in the adjacent layers. Loss factors corresponding to viscoelastic damping of flexible risers can be calculated by means of energy method combined with the theoretical model. Compared with the previous model, this theoretical model provides some more accurate results.